2022
DOI: 10.3390/catal12080878
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of 5-Acetoxymethylfurfural over Cu-Based Catalysts in a Flow Reactor: Effect of Cu-Al Layered Double Hydroxides Synthesis Conditions on Catalytic Properties

Abstract: Cu-containing layered double hydroxides (LDHs) were synthesized by a co-precipitation method at different reaction conditions, such as aging time, pH, precipitation rate and synthesis temperature. The effect of these parameters on the structure and chemical composition of the catalysts were investigated using a set of physical methods, including thermogravimetric analysis (TGA), X-ray diffraction (XRD), H2-TPR and in situ X-ray photoelectron spectroscopy (XPS). It allowed for checking of the reducibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Further experiments revealed that at the CO 3 2− /Al 3+ ratio of 0.5 and 0.76 and pH in the range of 9-10.5, the single-phase CuAl-LDH product is formed reproducibly regardless of the order of addition of reagents, the precipitation temperature, and the aging temperature of the mother liquor. At the same time, an increase in the aging temperature from 25 to 70 • C contributes to an increase in the crystallinity of the target CuAl-LDH, which is reflected in an increase in the intensity of diffraction peaks with a decrease in their width (Figure S1, [11]). Subsequent synthesis of CuAl-LDH in the carbonate form (containing CO3 2− anions in the interlayer space) was carried out using a typical co-precipitation procedure reported in [30,31]; solutions of aluminum and copper nitrates were added to an excess of Na2CO3 solution.…”
Section: Synthesis Of Cual-ldh By the Co-precipitation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further experiments revealed that at the CO 3 2− /Al 3+ ratio of 0.5 and 0.76 and pH in the range of 9-10.5, the single-phase CuAl-LDH product is formed reproducibly regardless of the order of addition of reagents, the precipitation temperature, and the aging temperature of the mother liquor. At the same time, an increase in the aging temperature from 25 to 70 • C contributes to an increase in the crystallinity of the target CuAl-LDH, which is reflected in an increase in the intensity of diffraction peaks with a decrease in their width (Figure S1, [11]). Subsequent synthesis of CuAl-LDH in the carbonate form (containing CO3 2− anions in the interlayer space) was carried out using a typical co-precipitation procedure reported in [30,31]; solutions of aluminum and copper nitrates were added to an excess of Na2CO3 solution.…”
Section: Synthesis Of Cual-ldh By the Co-precipitation Methodsmentioning
confidence: 99%
“…Further experiments revealed that at the CO3 2− /Al 3+ ratio of 0.5 and 0.76 and pH in the range of 9-10.5, the single-phase CuAl-LDH product is formed reproducibly regardless of the order of addition of reagents, the precipitation temperature, and the aging temperature of the mother liquor. At the same time, an increase in the aging temperature from 25 to 70 °C contributes to an increase in the crystallinity of the target CuAl-LDH, which is reflected in an increase in the intensity of diffraction peaks with a decrease in their width (Figure S1, [11]).…”
Section: Synthesis Of Cual-ldh By the Co-precipitation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bukhtiyarova et al [1] studied Cu-Al mixed oxides in the flow hydrogenation of 5-acetoxymethylfurfural into 5-(acetoxymethyl)-2-furanmethanol, focusing on the effect of synthesis conditions, such as pH, temperature, aging time and precipitation rate, on Cu-Al layered double hydroxides. Under optimized reaction conditions, the 2 h Cu-Al catalyst, which was prepared at a constant temperature of 70 • C, a pH of 9 and an aging time of 2 h, provided a 98% yield of 5-(acetoxymethyl)-2-furanmethanol.…”
mentioning
confidence: 99%